Methylation Levels of LINE-1 As a Useful Marker for Venous Invasion in Both FFPE and Frozen Tumor Tissues of Gastric Cancer - Min, Jimin; Choi, Boram; Han, Tae-Su; Lee, Hyuk-Joon; Kong, Seong-Ho; Suh, Yun-Suhk; Kim, Tae-Han; Choe, Hwi-Nyeong; Kim, Woo Ho; Hur, Keun; Yang, Han-Kwang (Molecules and cells, 2017)
Long interspersed nuclear element-1 (LINE-1) is a retrotransposon that contains a CpG island in its 5'-untranslated region. The CpG island of LINE-1 is often heavily methylated in normal somatic cells, which is associated with poor prognosis in various cancers. DNA methylation can differ between formalin-fixed paraffin-embedded (FFPE) and frozen tissues. Therefore, this study aimed to compare the LINE-1 methylation status between the two tissue-storage conditions in gastric cancer (GC) clinical samples and to evaluate whether LINE-1 can be used as an independent prognostic marker for each tissue-storage type. We analyzed four CpG sites of LINE-1 and examined the methylation levels at these sites in 25 FFPE and 41 frozen GC tissues by quantitative bisulfite pyrosequencing. The LINE-1 methylation status was significantly different between the FFPE and frozen GC tissues ( < 0.001). We further analyzed the clinicopathological features in the two groups separately. In the frozen GC tissues, LINE-1 was significantly hypomethylated in GC tissues compared to their corresponding normal gastric mucosa tissues ( < 0.001), and its methylation status was associated with gender, differentiation state, and lymphatic and venous invasion of GC. In the FFPE GC tissues, the methylation levels of LINE-1 differed according to tumor location and venous invasion of GC. In conclusion, LINE-1 can be used as a useful methylation marker for venous invasion in both FFPE and frozen tumor tissues of GC.